2017
DOI: 10.5812/ijhrba.59543
|View full text |Cite
|
Sign up to set email alerts
|

Depression as a Risk Factor for Relapse After Inpatient Opioid Detoxification: 1-Year Follow-Up Study

Abstract: Background: Opioid dependence is a complicated disorder in which multiple factors interact to influence initiation of use, repeated use, addiction, and relapse. Negative emotional states, such as anger, anxiety, depression, frustration, and boredom are also associated with the highest rate of relapse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…For better efficacy of treatment, our physicians should consider the adequacy of methadone dosage, especially in patients with history of multiple previous treatments. In our study, patients with history of psychiatric diseases had lower adherence to MMT which was compatible with similar studies [15][16][17][18][19]. Chalana et al [15] found after inpatient opioid detoxification, patients with higher score on the depression scale had higher rate of relapse.…”
Section: Discussionsupporting
confidence: 91%
“…For better efficacy of treatment, our physicians should consider the adequacy of methadone dosage, especially in patients with history of multiple previous treatments. In our study, patients with history of psychiatric diseases had lower adherence to MMT which was compatible with similar studies [15][16][17][18][19]. Chalana et al [15] found after inpatient opioid detoxification, patients with higher score on the depression scale had higher rate of relapse.…”
Section: Discussionsupporting
confidence: 91%
“…Depression is referred to at least two weeks of depressed mood, apathy, and lack of pleasure in everything (6). Chalana et al (2017) (7), in a one-year follow-up study of addicts on treatment, showed that people with recurrent relapses reported a depression score almost twice the other group, and more than 16% of them had very severe depression. Tendency to use drugs is a coping strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Opioid use disorder continues to be a significant public health problem around the world. Opioid addiction is a chronic relapsing condition with multiple complex consequences (1). Opioids can be divided into natural opioids (morphine, codeine, and thebaine), semi-synthetic opioids (heroin, hydromorphone, hydrocodone, and oxycodone), and fully synthetic opioids (fentanyl, pethidine, levorphanol, methadone, tramadol, and dextropropoxyphene) (2).In Malaysia, it is estimated that the prevalence of opioid demand for 2018was the highest compared to other substances (3).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted at a government hospital methadone center found that 36.5% of patients relapse 6 months after joining the MMT program (9). Globally, relapse among those who underwent detoxification programs ranges from 20% to 80% (1,13,16,20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation